Public opinion and correctional privatization - Frost, Natasha (Criminology & public policy, 2019)
Slightly more than half of all states and the federal government currently have contracted with private prison corporations for the incarceration of some of their correctional populations. We use the literature on privatization of prisons to argue that we know surprisingly little about the public's perception of this phenomenon. We summarize what is known from the thin body of research into public opinion in the correctional domain, and then we argue for an expanded research agenda to develop a more extensive (and nuanced) understanding of public perceptions in this context.